Combination and development of carbon filament tows: Application of coextrusion with long fiber-reinforced thermoplastics - Lin, M. C.; Lin, J. H.; Bao, L.
In this study, long fiber-reinforced thermoplastics (LFT)and coextrusion are applied to wrap carbon fiber tows in a thermoplastic polyurethane (TPU)outer layer. In this way, the proposed wrapped yarns have a sheath-core structure. Scanning electron microscopy observation reveals that TPU and carbon fiber tows form a physical combination that allows TPU to further enhance the tensile strength of carbon fiber tows by 35.87 percent , which is 19.62?±?1.88?MPa. The tensile strain of carbon fiber tows also improves. LFT and coextrusion are performed to produce successive carbon fiber tows that can be successfully fabricated into textiles, possessing good fabric flexibility. The technique of carbon fiber tows can be applied to mass production feasibility for the field of carbon fiber composites.